Islam and Tradition in Nanga Jajang: Social and Religious Practices Of the Malay Community - Ibrahim MS (Al-Albab, 2015)
Islam basically brings noble values in managing human relationship with God (hablumminallah). With these noble values, Islam teaches the way for humans to worship God. Meanwhile, traditions which are the rituals and customs of a society, is also an attempt to build a relationship with something other than human. Therefore, it is clear that Islam and traditions that are present in people’s behavior also bring certain values that are different from each other. In the Malay community of Nanga Jajang, Islam as a religion and religious rituals are inseparable from the traditional rituals. In fact, there are no clear boundaries between traditions and religious rituals in practice, as seen in ma`syiral jum`atan, acara begunting rambut (hair cutting ceremony), sunatan (circumcision), barobat kampung (traditional healing), etc. In social traditions, religion practices also run simultaneously such as reading the Qur’an and shalawat to the prophet. On the other hand, religious practices are also incorporated into elements of local traditions such as the hair cutting ceremony for infants, circumcision, etc., with a set of materials that are also found in social traditions. Similarly, the prayer used in the traditional healing appears to have the process of completion, even accommodation of Islamic values and traditions in the practice of the life the Malay community in Nanga Jajang.